apply Six Sigma in improving the quality of projects added expert system )Applied research( - خلف, بتول عطية; حاتم, اوس; محمد, محمد عبد الرزاق (Journal of Economics and Administrative Sciences, 2019)
Construction projects need methods and techniques to ensure the level of quality and commensurate with the level required and documented in the project contract. The quality of the project is affected by the quality of the inputs and accompanying procedures in the construction of the project.Al-Rumaitha residential project found that the quality of the concrete for the ceilings in the research sample (the roof of the third floor of buildings A25 and A26) and (roof of the second floor of buildings A27, A28, A29, A30, A31, A32 and A33) and roof of buildings A15 and A16 A19)) is not the required quality level.The idea of the research came after the need to improve the performance of Al-Rumaitha project in order to raise the quality. Some deviations have been detected in the measurement of compressive strength of the concrete used in casting ceilings, which lead to a level of quality below the level desired by the project.The aim of the research is to improve the quality of the concrete in the project and reduce the variance from the target quality. The Process capability and the Six Sigma technique of the DMAIC methodology is used as an improvement methodology. The principle of fragmentation of the project has also been taken to improve each phase separately whenever required.In addition, an expert system has been designed to facilitate the DMAIC quality improvement process as a program for the implementation of the first, second and third phases of the DMAIC methodology (definition, measurement and analysis( The fourth stage (improvement) is through proposals and changes that raise the efficiency of the work and the fifth phase is to monitor and control the improvements to maintain the level of Sigma reached.As well as the possibility of the application of Six Sigma is characterized by giving accurate results and good to improve the quality of the project. In addition to the possibility of documenting data and information of the examination, which provides a database that can be used by the expert system, which is designed to improve the quality of the project. The research concludes that the Six Sigma indicator contributes to making the quality of the concrete consistent and within the specified cost range. If the quality of the concrete is raised to the highest possible level, the CPk can be the most appropriate.